APPLICATION OF THE HABITUATION METHOD IN IMPROVING STUDENT LEARNING DISCIPLINE - Abdullah Abdullah; Umar Manshur (Educare : Jurnal Ilmu Pendidikan, 2023)
Discipline in learning is matters relating to an attitude that shows a willingness to comply or obey and support the provisions, rules, regulations, values, and rules that apply, in practicing and studying in learning but in reality our current education does not fully meet expectations. public. it is not uncommon for various educational problems to occur where there are students who violate school rules, due to the deterioration in learning, caused by the lack of discipline in student learning. This will greatly affect and have a negative impact on student learning activities. This study aims to describe the application of the habituation method in improving student learning discipline. This type of research uses a qualitative descriptive approach. Data Collection Methods in this study were obtained through observation, interviews, and documentation. The resulting data is then analyzed by researchers using three stages, namely reduction, data presentation, and drawing conclusions. Based on the results of this study, the authors found that the form of application of the habituation method in improving student learning discipline in educational institutions, namely by regulation, punishment, giving gifts, consistency and exemplary.